1997
DOI: 10.3109/00048679709073847
|View full text |Cite
|
Sign up to set email alerts
|

Media Depictions of Mental Illness: An Analysis of the Use of Dangerousness

Abstract: The study challenges the notion that media present negative depictions of mental illnesses either because journalists are poorly informed or because 'sensation sells'. It is concluded that media practices directed at engaging readers require the use of cases and a style of writing that forces readers to draw upon commonsense knowledge of mental illness to understand the text. It is argued that this is a deliberate effort to enlist readers as co-creators of the text and thereby increase their interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
99
4
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(112 citation statements)
references
References 17 publications
7
99
4
2
Order By: Relevance
“…As noted earlier, previous studies have found that mental illness is frequently presented by the media in a negative manner, and often in the context of crime and violence~Day & Page, 1986;Meagher, Newman, Fee, & Casey, 1995;Philo, McLaughlin, & Henderson, 1996;Allen & Nairn, 1997;Hazelton, 1997;Ward, 1997;Nairn, 1999;Wahl, Wood, & Richards, 2002!. For example, Ward~1997!…”
Section: Media Portrayalsmentioning
confidence: 99%
“…As noted earlier, previous studies have found that mental illness is frequently presented by the media in a negative manner, and often in the context of crime and violence~Day & Page, 1986;Meagher, Newman, Fee, & Casey, 1995;Philo, McLaughlin, & Henderson, 1996;Allen & Nairn, 1997;Hazelton, 1997;Ward, 1997;Nairn, 1999;Wahl, Wood, & Richards, 2002!. For example, Ward~1997!…”
Section: Media Portrayalsmentioning
confidence: 99%
“…This may be because adverse stories are the result not simply of media sensationalism, but of a more subtle collaboration between the assumptions of both journalist and reader (Allen & Nairn, 1997).…”
Section: Information Media and Social Attitudesmentioning
confidence: 99%
“…It is possible that portrayals of mental illness as being dangerous fulfil a fundamental human need to build distressing images into familiar narratives, regardless of their objective truth, in order to reduce the uncertainty that they provoke (Salter, 2001). Allen and Nairn (1997) demonstrate how the media exploits the pre-existing common sense of the consumer to construct such narratives, reaffirming established beliefs.…”
Section: The Power Of the Stereotypementioning
confidence: 99%